Building Resilience in Smallholder Dairy Farming: Integrating Enterprise Risk Management and Sustainability Dimensions in Indonesia - Uyun Erma Malika; Huda Ahmad Hudori; Rizal Perlambang CNAW Putra; Budi Prasetyo (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Smallholder dairy farming plays a crucial role in rural livelihoods and food security in developing countries, yet it is highly exposed to multidimensional risks that threaten its sustainability. While previous studies have examined agricultural risks and sustainability separately, limited attention has been given to how these risks interact to shape system resilience and adaptive capacity. This study aims to analyze resilience in smallholder dairy farming by integrating Enterprise Risk Management (ERM) with a multidimensional sustainability framework. A case study was conducted in Suci Village, Jember Regency, Indonesia, involving 30 respondents, including farmers, cooperative representatives, and agricultural officers. Data were collected through focus group discussions, semi-structured interviews, and field observations. Risks were identified and assessed using an ERM-based risk register matrix, evaluated through likelihood and impact scoring. The results were subsequently reinterpreted using a resilience framework, linking risk exposure, sensitivity, and adaptive capacity. The findings reveal that most risks are concentrated in the high and extreme categories, indicating a structurally vulnerable system with low baseline resilience. Risks are highly interconnected across ecological, economic, social, and technological dimensions, generating cascading effects that amplify system instability. Technological limitations and weak institutional capacity were identified as key constraints to adaptive capacity, further increasing vulnerability to recurring shocks. This study contributes to the literature by extending ERM from a risk classification tool into a resilience-oriented analytical framework. By integrating risk management with sustainability dimensions, the study provides a novel approach to understanding and strengthening resilience in smallholder agribusiness systems. The findings offer practical implications for developing integrated, context-specific strategies to enhance long-term sustainability and adaptive capacity in smallholder dairy farming.